Determinants of Bank Competitiveness in Digital Era A Case Study of South Korea - Young Jun Jin; Yanthi Hutagaol-Martowidjojo (Journal of Banking and Financial Economics, 2019)
Technical innovations in Digital Era provide the incentives for banks to redesign their business operations to enhance their competitiveness. Prior studies use financial indicator as factors that affect bank competitiveness, however, with the technology advancement, Information Communication Technology (ICT) become major factors in assessing banks’ competitiveness. The aim of this study is to analyze specific ICT factors, as well as financial factors, affecting bank competitiveness. This study examines all 17 commercial banks in South Korea. The ICT factors are measured by IT center operation and IT scandal released in news or mass media while the bank competitiveness is proxied by market share of each bank both in the borrowing and lending market. In addition, the study tests to retrospect financial indicators in comparison with ICT factors. Using OLS regression models, this study finds that, in the case of Korean commercial banks, ICT factors plays an importance role in bank competitiveness, however, the financial factors still have greater influences on market share than ICT factors. The implication is that banks should leverage the ICT innovation since there is a surge of ICT based non-bank financial service providers that have started to assume roles that have been traditionally played by banks. Furthermore, this study raises implications for policy makers to consider ICT security regulations in the banking market. This study contributes to the literatures by supporting the fact that the positive relationship between IT scandals and market share suggests implications to concentrated banking sectors and provides alarming with authority’s monitoring system.